2018
DOI: 10.1107/s2052252517018334
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced coherent sliding-layer transition in the excitonic insulator Ta2NiSe5

Abstract: The crystal structure of the excitonic insulator Ta 2 NiSe 5 has been investigated under a range of pressures, as determined by the complementary analysis of both single-crystal and powder synchrotron X-ray diffraction measurements. The monoclinic ambient-pressure excitonic insulator phase II transforms upon warming or under a modest pressure to give the semiconducting C-centred orthorhombic phase I. At higher pressures (i.e. >3 GPa), transformation to the primitive orthorhombic semimetal phase III occurs. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 30 publications
4
28
0
Order By: Relevance
“…6. Quite 8 unexpectedly, an electron band emerges above EF and the hole band below EF shifts upward. In addition, the bottom of the electron band and the top of the hole band seems to cross EF, and the system seems likely to be semimetallic.…”
Section: Temporal Evolution Of Tarpes Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…6. Quite 8 unexpectedly, an electron band emerges above EF and the hole band below EF shifts upward. In addition, the bottom of the electron band and the top of the hole band seems to cross EF, and the system seems likely to be semimetallic.…”
Section: Temporal Evolution Of Tarpes Spectramentioning
confidence: 99%
“…1c) 6,7 . This degeneracy can be partially lifted by the finite hybridisation between the two Ta chains.When the temperature decreases, Ta2NiSe5 undergoes a semiconductor-to-insulator transition at 328 K, accompanied by a structural distortion from orthorhombic to monoclinic symmetry 6,7,8 . According to the angle-resolved photoemission spectroscopy (ARPES) measurements in the equilibrium state, it has been found that the top portion of the valence band remarkably becomes flat below the transition temperature.…”
mentioning
confidence: 99%
“…Nev-ertheless, there is also a non-negligible coupling to the lattice. The 327 K second-order phase transition is accompanied by a lowering of the space group symmetry, as a shearlike distortion reduces the symmetry from orthorhombic to monoclinic [21][22][23] . Fano-like lineshapes in optical spectroscopy suggested a strong exciton-phonon coupling 18 , while timeresolved studies also show coherent oscillations associated with a coupling to phonon modes which persist for a longer time than the fast electronic timescales 24 .…”
mentioning
confidence: 99%
“…The valence band is mainly composed of Ni 3d orbitals with Se 4p admixture while Ta 5d orbitals dominate the conduction band [8]. Ta 2 NiSe 5 undergoes the second order phase transition at T C = 326 K accompanied by structural change from a high-T orthorhombic to a low-T monoclinic structure [7,9]. Angle-resolved photoemission spectroscopy study revealed that Ta 2 NiSe 5 exhibits a flattening valence band below T C , due to the formation of additional gap by exciton condensation [10,11].…”
Section: Introductionmentioning
confidence: 99%